2012
DOI: 10.1016/j.semarthrit.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Retinal Vasculitis Rarely Suffer from Systemic Vasculitis

Abstract: Objectives Systemic vasculitis is often mistakenly assumed to be a common cause of retinal vasculitis. We sought to determine the relationship between retinal vasculitis and systemic vasculitis. Methods A selected review was performed on 1390 charts of patients attending the uveitis clinic at the Oregon Health & Science University between 1985 and 2010. Included in the review were all patients with diagnoses commonly associated with retinal vasculitis and all patients who were diagnosed with a systemic vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 23 publications
0
49
2
2
Order By: Relevance
“…Retinal vasculitis typically occurs in association with intraocular inflammation as in sarcoidosis or as an isolated, idiopathic entity, but surprisingly, it rarely occurs in association with systemic forms of vasculitis 15. Patients with idiopathic retinal vasculitis are typically young adults with no signs or symptoms suggestive of an underlying systemic or ocular disease 17.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retinal vasculitis typically occurs in association with intraocular inflammation as in sarcoidosis or as an isolated, idiopathic entity, but surprisingly, it rarely occurs in association with systemic forms of vasculitis 15. Patients with idiopathic retinal vasculitis are typically young adults with no signs or symptoms suggestive of an underlying systemic or ocular disease 17.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported on 207 patients with retinal vasculitis who were evaluated at the Oregon Health & Science University, Casey Eye Institute, Portland, between the years 1985 and 2010 15 16. This report is based on a subset of that group, 56 patients with 101 affected eyes (45 patients were affected bilaterally and 11 patients were affected unilaterally).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RV can be idiopathic or with greater frequency associated to other ocular or systemic diseases 4. The most common diseases observed are Behçet’s disease, sarcoidosis and multiple sclerosis 5. In 2012, Rosenbaum et al reviewed the charts of 1390 patients with uveitis and found evidence of RV in 207 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The less common causes are in italic type [8][9][10][11]. [6]. These lesions may lead to loss of vision.…”
Section: Tablementioning
confidence: 99%